Jou Se Ngofa Ngare Philosophy In the History of Traditional Leadership in Ternate - Abas, Thalib; Boko, Yusri Ali; Bau, Suhartin Ode; Safi, Jamin (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This study seeks to elucidate: (1) The history of the Jou Se Ngofa Ngare philosophy (2) traditional leadership patterns in Jou Se Ngofa Ngare  philosophy in the Ternate Sultanate, (3) the relationship between the leader (sultan) and the people (bala) in the Jou Se Ngofa Ngare  philosophy in the Ternate Sultanate. This study employs historical methods and a qualitative approach, including stages of topic determination, heuristics, criticism, and historiography. Methods of collecting data for research include interviews, observation, and document analysis. In the process of analysis, data is reduced, presented, and conclusions drawn. The findings of the study indicate that the philosophy of Jou Se Ngofa Ngare cannot be determined as to when it emerged and who its originator was, but it is believed to have existed since the Momole era (pre-Islamic). The Sultanate of Ternate adhered to the tenets of Ma Jojoho Toma kitabullah (faith in accordance with the Qur'an of Allah) and Ma Jojoho Toma of Rasulullah hadith. The Sultan serves as both the head of state and the head of government of the Sultanate of Ternate. Under his guidance, the sultan was endowed with two distinct categories of rights: Idhin and Jaib Kolano. The philosophy of traditional leadership espoused by Jou Se Ngofa Ngare  delineates pluralistic relationships. Aside from that, the sultan and the army function as a unified unit whose prosperity and the sultan's success are mutually dependent.